AN ITERATIVE METHOD FOR FINITE FAMILY OF HEMI CONTRACTIONS IN HILBERT SPACE - Thakur,Balwant Singh (Universidad de La Frontera. Departamento de Matemática y Estadística., 2013)
We consider the problem of finding a common fixed point of N hemicontractions defined on a compact convex subset of a Hilbert space, an algorithm for solving this problem will be studied. We will prove strong convergence theorem for this algorithm.